Dietary Nicotinamide Mononucleotide, a Key NAD+ Intermediate, Alleviates Body Fat Mass and Hypertriglyceridemia by Enhancing Energy Expenditure with Promotion of Fat Oxidation and Hepatic Lipolysis and Suppressing Hepatic Lipogenesis in db/db Mice - Bungo Shirouchi; Sarasa Mitsuta; Mina Higuchi; Mai Okumura; Kazunari Tanaka (Metabolites)
Background/Objectives: Supplementation with nicotinamide mononucleotide (NMN), a key nicotinamide adenine dinucleotide (NAD+) intermediate, exerts anti-aging, anti-obesity, and anti-diabetic effects in animal experiments. However, previous studies have evaluated NMN supplementation using oral administration in drinking water or by intraperitoneal administration. No studies have reported whether NMN exerts beneficial effects when incorporated into the diet. The diet is a multicomponent mixture of many nutrients that may interact with each other, thus weakening the effects of NMN. In the present study, we evaluated whether dietary NMN intake protects obese diabetic db/db mice from obesity-related metabolic disorders, such as dyslipidemia, hepatic steatosis, hyperglycemia, and hyperinsulinemia. Methods: Five-week-old male db/db mice were randomly assigned to two groups and fed for four weeks either a control diet containing 7% corn oil and 0.1% cholesterol (CON group, n = 6) or a diet supplemented with 0.5% NMN (NMN group, n = 5). Results: After 4 weeks of feeding, dietary NMN intake alleviated obesity, hypertriglyceridemia, and hepatic triglyceride accumulation in db/db mice. Respiratory gas analysis indicated that dietary NMN intake significantly enhanced energy expenditure by suppressing carbohydrate oxidation and increasing fat oxidation after 3 weeks of feeding. Additionally, the suppression of the increase in plasma triglyceride (TG) levels by dietary NMN intake was attributable to a reduction in hepatic TG levels through the suppression of fatty acid synthesis and the enhancement of fatty acid β-oxidation in the liver. Furthermore, the improvement in hepatic fatty acid metabolism induced by dietary NMN intake was partially responsible for the significant increase in plasma adiponectin and soluble T-cadherin levels. Conclusions: This is the first report to show that dietary NMN intake but not oral administration in drinking water or intraperitoneal administration alleviates body fat mass and hypertriglyceridemia by enhancing energy expenditure, with preferential promotion of fat oxidation, the enhancement of hepatic lipolysis, and the suppression of hepatic lipogenesis in db/db mice.